Microwave assisted crystal growth of a new organic-decavanadate assembly: [V10O27(OH)] · 2(C6N2H14) · (C6N2H13) · (C6N2H12) · 2H2O - Yotnoi B. (2014)
Microwave synthesis was used to grow single crystals of a new organic-inorganic supramolecular assembly, [V10O27(OH)] · 2(C6N2H14) · (C6N2H13) · (C6N2H12) · 2H2O, in a very short time compared to the conventional solution technique. In order to generate crystals suitable for single crystal experiments, an equimolar mixture of reactants and a few hours of microwave heating are required. Although non-merohedral twinning is an inherent problem, the crystal structure can be solved and refined in the orthorhombic space group Pna21 with a = 20.972(4) Å, b = 10.3380(14) Å, c = 20.432(3) Å, Z = 4, with an excellent result, R(F2) = 0.0431. The assembly is hydrogen bond-assisted and built up of the monoprotonated decavanadate and 1,4-diazabicyclo[2.2.2]octane of various degrees of protonation. The number and location of protons on both the inorganic and organic motifs govern the formation of the extensive hydrogen bonding network, which in turn regulates the assembly architecture. © Springer Science+Business Media, LLC 2009.